The many ways of organic pest control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Producing food without pesticides. Local solutions to crop pest control in West Africa, LJ Fuglie. Church World Service-CTA copublication. 1998. 164 pp. CTA number 927. 20 credit points.